An Advanced Separator for Li–O2 Batteries: Maximizing the Effect of Redox Mediators. Issue 18 (12th May 2017) - Lee, Seon Hwa; Park, Jin‐Bum; Lim, Hyung‐Seok; Sun, Yang‐Kook
Abstract : Although Li–O2 batteries are promising next‐generation energy storage systems with superior theoretical capacities, they have a serious limitation regarding the large overpotential upon charging that results from the low conductivity of the discharge product. Thus, various redox mediators (RMs) have been widely studied to reduce the overpotential in the charging process, which should promote the oxidation of Li2 O2 . However, RMs degrade the Li metal anode through a parasitic reaction between the RM and the Li metal, and a solution for this phenomenon is necessary. In this study, an effective method is proposed to prevent the migration of the RM toward the anode side of the lithium using a separator that is modified with a negatively charged polymer. When DMPZ (5, 10‐dihydro‐5, 10‐dimethylphenazine) is used as an RM, it is found that the modified separator suppresses the migration of DMPZ toward the counter electrode of the Li metal anode. This is investigated by a visual redox couple diffusion test, a morphological investigation, and an X‐ray diffraction study. This advanced separator effectively maximizes the catalytic activity of the redox mediator. Li–O2 batteries using both a highly concentrated DMPZ and the modified separator exhibit improved performance and maintained 90% round‐trip efficiency up to the 20th cycle. Abstract : The performance of Li–O2 batteries with a redox mediator is improved by using a negatively charged polymer‐coated separator. Coating PEDOT:PSS on the GF/C separator mitigated the migration of the redox mediator to the Li metal anode, leading to a more than tenfold extension in cycle life with high round‐trip efficiency of 90%.